Aluminum oxide and zinc oxide induced nanotoxicity in rat brain, heart, and lung - Yousef, M I; Roychoudhury, S; Jafaar, K S; Slama, P; Kesari, K K; Kamel, M Ae-N (Physiological research, 2022)
Nanomaterials or nanoparticles are commonly used in the cosmetics, medicine, and food industries. Many researchers studied the possible side effects of several nanoparticles including aluminum oxide (Al2O3-nps) and zinc oxide nanoparticles (ZnO-nps). Although, there is limited information available on their direct or side effects, especially on the brain, heart, and lung functions. This study aimed to investigate the neurotoxicity, cardiotoxicity, and lung toxicity induced by Al2O3-nps and ZnO-nps or in combination via studying changes in gene expression, alteration in cytokine production, tumor suppressor protein p53, neurotransmitters, oxidative stress, and the histological and morphological changes. Obtained results showed that Al2O3-nps, ZnO-nps and their combination cause an increase in 8-hydroxy-2´-deoxyguanosine (8-OHdG), cytokines, p53, oxidative stress, creatine kinase, norepinephrine, acetylcholine (ACh), and lipid profile. Moreover, significant changes in the gene expression of mitochondrial transcription factor-A (mtTFA) and peroxisome proliferator activator receptor-gamma-coactivator-1alpha (PGC-1alpha) were also noted. On the other hand, a significant decrease in the levels of antioxidant enzymes, total antioxidant capacity (TAC), reduced glutathione (GSH), paraoxonase 1 (PON1), neurotransmitters (dopamine - DA, and serotonin - SER), and the activity of acetylcholine esterase (AChE) in the brain, heart, and lung were found. Additionally, these results were confirmed by histological examinations. The present study revealed that the toxic effects were more when these nanoparticle doses are used in combination. Thus, Al2O3-nps and ZnO-nps may behave as neurotoxic, cardiotoxic, and lung toxic, especially upon exposure to rats in combination.
Keywords: Animals; kovové nanočástice; Antioxidants; Lung; oxidační stres; Aluminum Oxide; Nanoparticles; acetylcholin; Oxidative Stress; Metal Nanoparticles; oxid zinečnatý; mozek; nanočástice; Zinc Oxide; Brain; Acetylcholine; antioxidancia; krysa rodu Rattus; plíce; zvířata; Rats; oxid hlinitý